The potentials for corporatization of public hospitals: The case of Egypt - Abdelaleem, Mohamed Fayek (AUC Knowledge Fountain, 2017)
With changing health landscape across the globe, increasing burden of chronic diseases, increasing citizens expectations that accompanied by cost limitations, health reform becomes inevitable for Egyptian health system to maximize benefits and overcome challenges. Reform might include healthcare service provision, health policies, workforce planning or public health programs strategies. New Public Management concepts and principles represent the basis for many of reform plans since its emerging in the early 1990s. Many countries have used New Public Management guiding principles to shape its health reform program. Egypt is undergoing a reform plan across the whole sectors through Egypt 2030 plan announced by Ministry of Planning and Administrative reform. The reform plan has identified a set of goals for the health sector to achieve and another set of indicators to measure the progress and level of achievement. This paper presents corporatization of public hospital as a tool that can fit into the new reform program. With the execution of universal health coverage, the autonomy of hospitals will help to achieve the targeted level of performance, efficiency, and quality of services. The main challenge facing implementation is the high percentage of poverty in Egypt and their dependency on the government hospitals to get healthcare services. Transforming these hospitals into revenue generating organization will affect accessibility except there is a social insurance scheme that can protect poor against the commercialization of healthcare services. Research question: is corporatization improving performance, increasing accessibility and enhancing the quality of healthcare services? Methodology: qualitative research where semi-structured interviews were conducted with healthcare professional and system experts locally and globally to get their views on the feasibility of implementation of such reform in Egypt. Conclusion: corporatization of public hospitals in Egypt represents a fair organizational reform strategy for Egyptian health system to increase efficiency and satisfaction. Yet, a rigorous readiness assessment of the system components (regulations, providers, payers, and beneficiaries) should be executed to measure the readiness for implementation.